Effect of foot reflexology on brain corresponding areas during simple reaction time in healthy adults. - Srisupornkornkool, K.; Punyapuck, J.; Inprang , T.; Nakdee , K.; Boonyarom, O.; Somthavil, S. (Chulalongkorn Medical Journal, 2023)
Background : The feet have reflexological areas that correspond with different parts of the body. When different positions on the feet are stimulated, changes in the function of the corresponding organs happen. Objective : To investigate the effect of reflexology on the brain’s corresponding areas on simple reaction time in healthy adults. Methods : Twenty-four healthy female participants, aged 21 - 30 years, were randomly assigned to experimental group (foot reflexology on corresponding brain areas, n = 12) and control group (light touch on corresponding brain areas, n = 12). The participants were measured simple reaction time of the right and left hands. Results : This results showed significant difference in simple reaction time after foot reflexology and light touch on brain corresponding areas (P <0.05). There was no significant difference in simple reaction time between testing by right and left hand. Also, there was no significant difference in simple reaction time between the experimental and control groups. Conclusion : Both interventions of foot reflexology and light touch on brain’s corresponding areas are able to decrease simple reaction time.